Improving Students’ Vocabulary Mastery on Synonyms through the Application of Think Pair Share (TPS) Technique - Anna Stasya Prima Sari; Novalina Sembiring; Kwalitas Wau (Budapest International Research and Critics University, 2022)
This Classroom Action Research (henceforth, CAR) is mainly carried out to prove that the application of Think Pair Share (henceforth, TPS) technique is able to improve the students’ vocabulary mastery on synonyms and to describe the students’ responses towards the learning teaching processes of vocabulary mastery on synonyms through the application of TPS technique. This CAR was performed in two cycles in which each cycle consisted of three meetings excluded the pre-test and the post-test. The subjects of this research are the fifth semester students of English Language Education Study Program, Faculty of Teachers Training and Education, Universitas Katolik Santo Thomas in the Academic Year of 2021/2022. There are 21 students as the research subjects. The quantitative data analysis shows that the mean of the students’ score in the pre-test, formative test, and post-test increases continually after TPS technique was implemented in the learning teaching processes of English synonyms. The students’ total score in the pre-test is 1.252 and the pre-test mean is 59.62. The students’ total score in the formative test is 1.572 and the formative test mean is 74.86. The students’ total score in the post-test is 1.756 and the post-test mean is 83.61 There are five students (23.8%) who attained score >75 in the pre-test, ten students (47.6%) who attained score >75 in the formative test, and 17 students (81%) who attained score >75 in the post-test. The qualitative data analysis shows that the students are more active and enthusiastic in learning and mastering English synonyms after TPS technique was applied. The students gave positive responses towards the application of TPS technique in the learning teaching processes of vocabulary mastery on English synonyms. The researchers recommend that English lecturers/teachers implement TPS technique in order to improve their students’ vocabulary mastery on English synonyms.